Event-triggered predictive control of high-speed trains under virtual coupling - Jianliang Xu; Zhen Sui; Xiaohua Wei; Feng Xu (Automatika)
To address the control problem of high-speed trains operating under virtual coupling in actual communication environments, an event-triggered multi-trains cooperative tracking predictive control method is proposed considering the limited available resources of the system. Firstly, a multi-trains tracking model is established based on train dynamic equations, and the optimal tracking control problem is formulated according to the train running mechanism. Secondly, addressing the low computational efficiency and resource wastage in model predictive control, an event-triggered mechanism is introduced to enhance system real-time performance by incorporating judgment conditions during optimization problem-solving. Furthermore, the feasibility and stability of this control method are validated through theoretical analysis. Simulation results indicate that the speed and distance root-mean-square errors of the multi-trains obtained by the proposed control method are 6.25×10−4 and 1.8×10−4 respectively, indicating that the proposed method has good control and tracking performance. With the increase of trigger parameters, the number of triggers is reduced from 2500 to 799, and the calculation time is also reduced by about 51.7%, which further improves the resource utilization of the control system. It can be seen that the control method in this paper can well solve the multi-trains tracking control problem under the condition of resource limitation.